Survey on risk factors for chronic diseases in college students - doi:10.5020/18061230.2007.p168 - Vívian Saraiva Veras; Luciana Zaranza Monteiro; Camila Aparecida Pinheiro Landim; Antônia Tayana da Franca Xavier; Mônica Helena Neves Pereira Pinheiro; Renan Magalhães Montenegro Júnior (Universidade de Fortaleza, 2012)
The study proposed to identify the risk factors for diabetes mellitus (DM), systemic arterial hypertension (HAS) and cardiovascular diseases (DCV) in college students of a private institution in the city of Fortaleza. Two hundred students joined in the study, being submitted to an evaluation survey, in which were obtained data on: sex, age, history of tobacco use, alcoholism, sedentariness and family antecedents of DM, HAS, hypercholesterolemia and ischemic event. Those that presented three or more risk factors for DM, HAS and DCV being then, directed for accomplishment of anthropometric evaluation, capillary glucose measure and measurement of arterial pressure. The sample consisted of 172 students (128F/44M). The results pointed out that 121 (70.3%) of the students did not practice physical activities, 124 (72.1%) of the subjects presented family antecedents for DM, 131 (76.2%) for HAS, 104 (60.5%) for hypercholesterolemia and 91 (52.9%) for previous ischemic event, 43 (25%) presented overweight and 10 (5.9%) first-degree obesity, 30 (17.5%) had arterial pressure ? 130/60 mmHg. The results indicate the need for educational programs in the studied institution aiming at health education and prevention of chronic diseases.